Knowledge management system architecture for organizational learning with collaborative environment - 260856 Rusli Abdullah (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Doktor Falsafah (Sains Komputer) -Universiti Teknologi Malaysia, 2005